(3QSGdI dHYV GdQgHGf ChOYgG dhdOgs
(3ChdgG (B:s
(3bGd jG Hfi MaX gPg GdQSGdI hdGJaT dGeQgG dZjQ eSJMbgG hGYde jG Hfi EfgG gi GdMceI GdJi ChOYgG Gddg SHMGfg hJYGdi dGfHjGFg s
(3BNQgG (B:s
(3eQcHI ai HjJ aMe jSjQ YOOg YTQ aMeGJ hPcQ Cf gPG jYGO eG bWQ Ydi eG Hbi SHY OaYGJ hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3HYV GdQgHGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs